Enucleation versus hepatectomy for hepatic hemangiomas: A meta-analysis - Jiang, Bin; Shen, Zheng-Chao; Fang, Xiao-San; Wang, Xiao-Ming (Frontiers in Surgery, 2022)
Objective: Comparing the safety and efficacy of enucleation and hepatectomy for the treatment of hepatic hemangioma (HH). Methods: A systematic literature search was conducted to identify studies evaluating enucleation versus hepatectomy for HH from database creation to February 2022. Extraction of the data involved in this study from the literature. The differences between the two surgical approaches were evaluated by comparing and analyzing the relevant data by means of meta-analysis. Results: A total of 1384 patients (726 underwent enucleation, and 658 with hepatectomy) were included in our meta-analysis from 12 studies. Enucleations were associated favorable outcomes in operation time (MD: -39.76, 95% CI: -46.23, -33.30), blood loss (MD: -300.42, 95% CI: -385.64, -215.19), length of hospital stay (MD: -2.33, 95% CI: -3.22, -1.44) and postoperative complications (OR:0.57, 95% CI: 0.44 to 0.74). There were no differences between the groups in patients needing transfusion (OR:0.85, 95% CI: 0.50, 1.42), inflow occlusion time (MD: 1.72, 95% CI: -0.27, 3.71) and 30-d postoperative mortality (OR:0.23, 95% CI: 0.02 to 2.17). Conclusion: Compared to hepatectomy, enucleation is superior to reducing the postoperative complications, blood loss and operation time, and to shortening length of hospital stay. Enucleation has similar inflow occlusion time, 30-d postoperative mortality, and patients needing transfusing to hepatectomy.